RELATIONSHIP BETWEEN ATTITUDE TOWARD STEM AND COMPUTATIONAL THINKING ABILITY IN MATHEMATICS LEARNING OF ELEMENTARY SCHOOL STUDENTS - Suryaningsih, Tri (PD PGMI se Indonesia, 2023)
Computational Thinking (CT) plays an important role in Science, Technology, Engineering, Mathematics (STEM) fields. However, whether Attitude toward STEM is related to CT skills is still unknown. The purpose of the study was to determine whether there is a relationship between Attitude Toward STEM and Computational Thinking skills in mathematics learning of elementary school students. This research is a correlational quantitative research that measures the relationship between two variables. The research was conducted at SDN Gandaria Utara 03 in class IVA and IVB. Simple random sampling technique was used to determine the research sample. The instruments in this study used a questionnaire to measure Attitude Toward STEM and a test instrument to measure Computational Thinking ability. The instruments in this study were measured for validity and reliability before use. Data analysis techniques using linear regression statistical tests. The results showed that Attitude toward STEM is related to Computational Thinking ability. From the results of data analysis, the regression model equation is Y = 19.635 + 0.387x. The coefficient of determination or R2 of 0.805 means that the Attitude Toward STEM variable simultaneously has an influence of 80.5% on the Computational Thinking ability variable